Governing medical tourism : the roles of Singaporean government - Pitakdumrongkit, Kaewkamol (2021)
This article seeks to shed light on a question: “What explains a nation’s medical tourism?” This paper focuses on the roles played by a central government in shaping the industry, espescially how it balances the advantages and disadvantages of pursuing medical tourism, which has been under-examined. I attempt to fill such intellectual gap by investigating the roles in the Singaporean government in affecting the country's medical tourism. Via this case, I demonstrate how the state’s authorities crafted the rules and regulations to promote the sector and simultaneously cope with the adverse effects that the industry brings to the nation. Insights from my analysis not only extends the existing literatures on the development of medical tourism and roles of domestic political institutions in shaping states’ policy outcomes, but also provides practitioners with lessons useful for crafting effective policies to sustain their countries’ pursuit of medical tourism.